High versus low vancomycin serum trough regimen for Gram-positive infections: a meta-analysis. (August 2015) - Meng, Long; Fang, Yun; Chen, Yongfei; Zhu, Huaijun; Long, Rui
<x content-type="archive" xml:space="preserve">Abstract</x> This study aimed to evaluate the impact of high vancomycin serum trough concentrations (≧15 mg/l) on clinical outcomes and nephrotoxicity among adult subjects. We searched MEDLINE, Cochrane Library, and CNKI systematically. A total of 17 studies were included. Meta-analysis found that high trough group showed no significant difference comparing to low trough group in treatment failure [relative risk (RR) 0·91, 95% confidence interval (CI) 0·67–1·24; P = 0·57] and all-cause mortality (RR 1·14, 95% CI 0·81–1·59; P = 0·46). However, the high trough concentrations were associated with lower treatment failure in bacteremia subgroup (RR 0·72, 95% CI 0·59–0·88; P = 0·001). High trough concentrations were associated with an increased risk of vancomycin-induced nephrotoxicity (RR 2·06, 95% CI 1·52–2·79; P<0·00001). Our meta-analysis indicates that high trough concentrations were not significantly superior to low trough concentrations in lowering treatment failure and mortality. Moreover, high trough concentrations significantly increased the risk of nephrotoxicity.